The relationship between green innovation, foreign direct investment, and sustainable development in the context of geopolitical risk - Tran , Tho Dat; Nguyen , Vu Hung; Tran, Thi Kim Oanh; Nguyen , Thanh Liem; Wong, Wing-Keung (Journal of Finance - Marketing Research, 2026)
This study examines the effects of green innovation (GI), foreign direct investment (FDI), and geopolitical risk (GPR) on sustainable development (SD) in the context of increasing global uncertainty. A Bayesian regression approach is applied to panel data from 33 countries over the period 2010–2021 to better capture uncertainty and structural heterogeneity in the data. The results indicate that GI has a positive impact on sustainable development, with a posterior probability of 59.79%; however, its average effect remains unstable when GPR is not taken into account. In contrast, FDI does not demonstrate a clear role in promoting SD and tends to generate adverse effects under average conditions, lending support to the “pollution haven” hypothesis. GPR exhibits a pronounced negative effect on SD with a posterior probability of 100%. Importantly, the findings reveal a strong moderating effect of GPR: under higher GPR, the positive impact of GI on SD is significantly strengthened, indicating that GI plays a dual role as both an environmental driver and a buffer enhancing resilience to external shocks. Conversely, GPR exacerbates the negative implications of FDI for SD. These results highlight the critical role of GPR in shaping the effectiveness of GI and FDI, offering important policy insights for fostering SD in an increasingly uncertain global environment.